Absorbance dependence of ZnO thin films on post-heating temperature. Issue 6 (March 2021) - Sugihartono, I; Putri, A R; Tiam, T S; Cahyana, U; Handoko, E; Budi, S; Fahdiran, R; Rustana, C; Susila, A B; Budi, E
Abstract: We have prepared ZnO thin films on indium tin oxide (ITO) glasses using dip-coating at room temperature. Post-heating has been performed by different temperatures i.e. 450 °C, 500 °C, 550 °C, and 600 °C under atmosphere ambient. The effect of post-heating temperature on the structural properties and absorbance of ZnO thin films have been investigated. Structurally, we observed ZnO thin films under a post-heating temperature of 450 °C, 500 °C, and 550 °C have polycrystalline hexagonal wurtzite structure. Meanwhile, at the temperature of 600 °C, it has an amorphous structure. Optical absorbance spectra of ZnO thin films confirmed that amorphous structure has the highest intensity compared to polycrystalline hexagonal wurtzite structure.